2020
DOI: 10.1111/nph.16907
|View full text |Cite
|
Sign up to set email alerts
|

Rapid starch degradation in the wood of olive trees under heat and drought is permitted by three stress‐specific beta amylases

Abstract: Summary Carbon reserve use is a major drought response in trees, enabling tree survival in conditions prohibiting photosynthesis. However, regulation of starch metabolism under drought at the whole‐tree scale is still poorly understood. To this end, we combined measurements of nonstructural carbohydrates (NSCs), tree physiology and gene expression. The experiment was conducted outside on olive trees in pots under 90 d of seasonal spring to summer warming. Half of the trees were also subjected to limited wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 94 publications
1
26
0
Order By: Relevance
“…According to studies using transgenic and mutant plants, beta-amylase seems to be important for normal degradation of the transient starch accumulated in chloroplasts [76]. Meanwhile, beta-amylases possibly facilitating the rapid starch degradation under heat and drought [77]. In this study, we found that the PSG expression levels involved in beta-amylase for O. longilobus was signi cantly higher than those for O. taihangensis (Figure 4A).…”
Section: Adaptability Of Psgsmentioning
confidence: 48%
See 1 more Smart Citation
“…According to studies using transgenic and mutant plants, beta-amylase seems to be important for normal degradation of the transient starch accumulated in chloroplasts [76]. Meanwhile, beta-amylases possibly facilitating the rapid starch degradation under heat and drought [77]. In this study, we found that the PSG expression levels involved in beta-amylase for O. longilobus was signi cantly higher than those for O. taihangensis (Figure 4A).…”
Section: Adaptability Of Psgsmentioning
confidence: 48%
“…In this study, we found that the PSG expression levels involved in beta-amylase for O. longilobus was signi cantly higher than those for O. taihangensis (Figure 4A). Starch degradation as a major response in conditions prohibiting photosynthesis or prolonged drought [77], therefore, O. longilobus seems better adapted to weak light or drought conditions than O. taihangensis.…”
Section: Adaptability Of Psgsmentioning
confidence: 99%
“…According to studies using transgenic and mutant plants, beta-amylase seems to be important for normal degradation of the transient starch accumulated in chloroplasts [ 76 ]. Meanwhile, beta-amylases possibly facilitating the rapid starch degradation under heat and drought [ 77 ]. In this study, we found that the PSG expression levels involved in beta-amylase for O. longilobus was significantly higher than those for O. taihangensis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…5 A). Starch degradation as a major response in conditions prohibiting photosynthesis or prolonged drought [ 77 ], therefore, O. longilobus seems better adapted to weak light or drought conditions than O. taihangensis .…”
Section: Discussionmentioning
confidence: 99%
“…sylvestris) olive trees provide an effective way of identifying the molecular mechanisms involved in morphogenesis ( Cruz et al, 2016 ; Unver et al, 2017 ; Rao et al, 2021 ). Researches on fruit development, fatty acid synthesis, and response to drought or salt or heat is plentiful ( Rao et al, 2019 ; Tsamir-Rimon et al, 2020 ; Valente et al, 2020 ), but little is known about the response of the olive tree to aluminum stress.…”
Section: Introductionmentioning
confidence: 99%